Uvedba laboratorijskega spremljanja respiratornega sincicijskega virusa v Sloveniji - Sočan, Maja (Zdravstveno varstvo, 2008)
Background: Respiratory syncytial virus (RSV) is the most common causative agent of acute lower respiratory tract infections in infants and young children worldwide. RSV causes bronchiolitis with life-threatening complications. The majority of RSV infections occur in the winter period. A humanized monoclonal antibody palivizumab was developed to prevent RSV diseaseand RSV hospitalization in high-risk children. The availability of palivizumab for preventing RSV infection stresses the importance of RSV surveillance, which should involve monitoring the onset, peak and termination of the RSV season, and determining optimal time for palivizumab administrationin children who fulfill the criteria for RSV prophylaxis. Material and methods: In Slovenia, laboratory RSV surveillance was introduced in the 2006/2007 RSV season. All public health laboratories in the country agreed to participate in the programme. RSV surveillance is implemented in the following laboratories: regional public health institutes of Maribor, Celje, Kranj, Koper and Novo mesto, the laboratory of virology of the Institute of Public Health, the microbiology laboratory of the Nova Gorica Hospital and the laboratory of the Institute of Microbiology and Immunology, Medical Faculty, University of Ljubljana. All these laboratories enter the number of patients tested and the number of RSV positive cases on a password-protected web site on a weekly basis. Results: From October 2006 to April 2007, 3,796 patients were tested for RSV infection, and 719 (18.9 %) were found to be positive. The first RSV positive samples were confirmed in week 42. The percentage of positive samples was steadly increasing and reachedits peak at the end of January/beginning of February (week 5, year 2007). The highest incidence rate of acute respiratory infections in children less than four years of age was recorded in the same week. Three weeks later, during the period of intensive circulation of influenza A virus, acute respiratory infections in this age group reached approximately the same incidence rate as during the full-blown RSV epidemic. Conclusion: Laboratory based RSV surveillance has an important supportive role in defining the timingof palivizumab administration in children who fulfill the criteria for prophylaxis. We plan to continue RSV surveillance in forthcoming seasons.
Keywords: child; dihala; infekcije; laboratorijska diagnostika; otroci; respiratorni sincicijski virus